Organization of Project Work that Forms Small Research Skills of Students in Elementary Mathematics Classes (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In the article describing the method of using project work for the development of creative ideas and creative skills, the improvement of knowledge.